PEMANFAATAN MEDIA KIT IPA DI SEKOLAH DASAR KECAMATAN SIULAK MUKAI - Angreni, Siska; Sari, Rona Taula (Jurnal Pendidikan Dasar, 2022)
This study aims to describe the utilization of Integrated Instrument Component media (KIT) in science learning in several SD Negeri Siulak Mukai Sub districts. The method used is descriptive method with the survey research firm. Instruments used include observation sheets, questionnaires, and interview guides. Based on data analysis, it is found that the utilization of Integrated Instrument Component media (KIT) science in some SD Negeri Siulak Mukai sub-districts is not maximal yet. This is due to the lack of knowledge and skills of teachers in utilizing Integrated Instrument Component media (KIT) science, elusive and applicable guidebooks, inadequate teaching hours because the labs require a relatively long time, have not been trained in the use of Instrument Component media (KIT) science.